Electrodes: Advanced Extremely Durable 3D Bifunctional Air Electrodes for Rechargeable Zinc‐Air Batteries (Adv. Energy Mater. 6/2014). Issue 6 (April 2014) - Lee, Dong Un; Choi, Ja‐Yeon; Feng, Kun; Park, Hey Woong; Chen, Zhongwei
<x xml:space="preserve">Abstract</x> Advanced air electrodes composed of cobalt oxide nanowire arrays grown directly onto stainless steel mesh current collectors, reported by Zhongwei Chen and co‐workers in article number 1301389, show remarkable rechargeable zinc‐air battery performance. Specifically, the electrode shows bifunctional activity towards both the oxygen reduction and evolution reactions, demonstrating up to 600 h of cycling stability utilizing air under ambient conditions. This paves the way for the application of this promising battery technology in electric vehicles, smart‐grid scale energy storage, and portable electronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>